Dry-method battery pole piece, preparation method thereof and battery comprising pole piece

Through the multi-dimensional structural design of the composite current collector and electrode membrane, the problems of bonding strength, wettability and conductivity of dry-process battery pole pieces are solved, high-performance battery pole piece preparation is achieved, and the battery cycle stability and ion transmission efficiency are improved.

CN120727754AActive Publication Date: 2025-09-30HIGH ENERGY DIGITAL MFG (XIAN) TECH CO LTD

Patent Information

Application Number
CN202511231996.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2025-09-30
Estimated Expiration
2045-09-01

AI Technical Summary

Technical Problem

Existing dry-process battery electrodes have problems such as weak interface bonding between the current collector and the electrode membrane, insufficient electrolyte wettability, serious side reactions at the positive electrode material interface, poor negative electrode conductivity, and severe volume expansion, resulting in poor battery performance.

Method used

A composite current collector design is adopted, including a metal base layer, a mesoporous carbon-MOF composite transition layer and a conductive polymer transition layer, to form a gradient pore and deposit an Al2O3 coating. Combined with a magnetic field-assisted directional arrangement of carbon fiber and carbon nanotube networks, the pole piece is prepared by gradient pressing and plasma treatment.

Benefits of technology

It significantly improves the interface bonding strength of the electrode and the electrolyte infiltration speed, improves the conductivity and cycle stability, optimizes the ion transmission efficiency, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120727754A_ABST
    Figure CN120727754A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a dry battery pole piece, a preparation method thereof and a battery comprising the pole piece, and the method comprises the following steps: S1, preparing a composite current collector; s2, preparing an electrode film: S21, preparing a positive electrode film, and S22, preparing a negative electrode film; s3, preparing a pole piece green body: sequentially laminating the positive electrode film, the composite current collector and the negative electrode film, and carrying out gradient pressure rolling at 120-180 DEG C, linearly increasing the pressure from 5-10MPa at the edge to 15-20MPa at the center, and controlling the rolling speed to be 1-3m / min, so as to form the pole piece green body; and S4, preparing the dry-method battery pole piece. The composite current collector adopts a three-layer substrate structure of a metal substrate layer, mesoporous carbon, an MOF composite transition layer and a conductive polymer transition layer, gradient pores are formed through laser drilling, and an AlO nano coating is deposited to enhance interface bonding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a dry-process battery pole piece, a preparation method thereof, and a battery comprising the pole piece. Background Art

[0002] Lithium-ion batteries, with their advantages of high energy density and long cycle life, are widely used in new energy vehicles, energy storage systems, and other fields. As the core component of a battery, the structure and performance of the electrode sheet directly determine its overall performance. Dry-process preparation, due to its advantages such as the lack of organic solvents, short process steps, and environmental friendliness, has become a key development direction in electrode sheet preparation technology.

[0003] Existing dry-process battery electrode technology has many shortcomings: the interface bonding between the current collector and the electrode membrane is weak and prone to peeling; the electrolyte has insufficient wettability on the dry-process electrode, affecting ion transmission; high-nickel positive electrode materials are prone to interfacial side reactions and have poor cycle stability; silicon-based negative electrodes have poor conductivity and severe volume expansion; and the uneven distribution of the conductive network leads to high internal resistance of the electrode.

[0004] For this purpose, an improved dry-process battery pole piece, a preparation method thereof, and a battery including the pole piece are designed. Summary of the Invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a dry-process battery electrode, a method for preparing the same, and a battery comprising the electrode to solve the above-mentioned problems in the background art.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a dry battery electrode comprises the following steps: S1. Preparation of a composite current collector: depositing a mesoporous carbon-MOF composite transition layer and a conductive polymer transition layer on the surface of a metal substrate to form a composite current collector substrate, creating gradient pores throughout the composite current collector substrate, and depositing an Al2O3 coating on the inner wall of the gradient pores to obtain a composite current collector; S2. Preparation of electrode film: comprising the following steps, S21. Preparation of positive electrode film: The core-shell structure positive electrode active material, carbon fiber, carbon nanotubes and composite binder are dry mixed in a high-speed mixer at 1500-2000 rpm for 3-5 hours; the mixed material is aligned with the aid of a 0.1-0.5T magnetic field, and fiberized at 150-200°C for 2-5 hours, and pressed into a 50-300μm thick positive electrode film; S22. Anode membrane preparation: MXene-modified anode active material, carbon fibers, carbon nanotubes, and a composite binder were dry-mixed in equal proportions in a high-speed mixer at 1500-2000 rpm for 3-5 hours. The mixed materials were aligned in a 0.1-0.5 T magnetic field, fiberized at 150-200°C for 2-5 hours, and pressed into a 50-300 μm thick anode membrane. S3: Preparation of electrode sheet: The positive electrode film, composite current collector, and negative electrode film are stacked in sequence, and subjected to gradient pressure rolling at 120-180°C, with the pressure linearly increasing from 5-10 MPa at the edge to 15-20 MPa in the center, and the rolling speed is 1-3 m / min to form the electrode sheet; S4: Preparation of dry-process battery pole pieces: The pole piece blank is subjected to plasma treatment for 30-120s at a power of 50-150W using a mixed gas of argon and oxygen in a volume ratio of 3:1. After the treatment, it is placed in a Li2SO4 solution with a concentration of 0.1mol / L and activated at a constant voltage of 0.5V for 30min to obtain a dry-process battery pole piece.

[0007] Furthermore, the metal base layer in step S1 is aluminum foil or copper foil. When preparing the positive electrode sheet, an aluminum foil with a thickness of 5-20 μm is selected, and when preparing the negative electrode sheet, a copper foil with a thickness of 5-20 μm is selected.

[0008] Furthermore, the preparation method of the mesoporous carbon-MOF composite transition layer described in step S1 includes: dispersing the mesoporous carbon precursor and MOF powder in ethanol in a mass ratio of 7:3, and after coating, calcining at 300-500°C in a nitrogen atmosphere for 2-4 hours to form a mesoporous carbon-MOF composite transition layer. The thickness of the mesoporous carbon-MOF composite transition layer is 2-5 μm, and the mesopore size is 2-5 nm.

[0009] Furthermore, the conductive polymer transition layer in step S1 is a composite layer of poly (3,4-ethylenedioxythiophene)-polystyrene sulfonate and graphene, wherein the mass of graphene accounts for 5%-10% of the total mass of the conductive polymer transition layer, and the thickness of the conductive polymer transition layer is 1-5 μm.

[0010] Furthermore, the gradient pores are processed throughout the composite current collector substrate, including: using a laser drilling device, with the metal base layer side as the starting end and the conductive polymer transition layer side as the ending end, controlling the laser power to linearly decrease from 50-60W to 20-30W, while maintaining a drilling rate of 100-200 holes / second, so that the pore size formed increases linearly from 5-20μm on the metal base layer side to 50-200μm on the conductive polymer transition layer side.

[0011] Furthermore, the Al2O3 coating is deposited on the inner wall of the gradient pore, comprising: using trimethylaluminum and water as precursors, depositing 5-15 cycles by atomic layer deposition technology at a temperature of 100-150°C to form an Al2O3 nano-coating with a thickness of 1-3nm.

[0012] Furthermore, the method for preparing the core-shell structure positive electrode active material in step S2 includes: dispersing high nickel ternary material powder in a lithium iron phosphate precursor solution, hydrothermally reacting at 180-220° C. for 6-12 hours, and then calcining to obtain a core-shell structure positive electrode active material with the high nickel ternary material as the core and the lithium iron phosphate material as the shell; In step S2, the carbon fibers and carbon nanotubes are aligned in a 0.1-0.5 T magnetic field to form an orderly interwoven oriented conductive network, wherein the oriented conductive network is formed by interweaving carbon fibers with an aspect ratio of 50-100 and carbon nanotubes with a diameter of 10-20 nm in a mass ratio of 3:1, with the carbon fibers having a length of 5-20 μm and the carbon nanotubes having a length of 10-50 μm. The preparation method of the MXene-modified negative electrode active material in step S2 includes: mixing the silicon-carbon composite material and graphite in a mass ratio of 1:3-1:5, adding 1-3% by mass of MXene nanosheets and modifying them by ball milling to obtain the MXene-modified negative electrode active material.

[0013] Furthermore, the composite binder is composed of polytetrafluoroethylene and multi-arm polyethylene glycol in a mass ratio of 3:1, and the total mass of the composite binder accounts for 2%-4% of the total mass of the mixed materials.

[0014] The present invention also provides a dry-process battery electrode, which is prepared by the above-mentioned preparation method, comprising: A composite current collector, comprising, from the inside out, a metal base layer, a mesoporous carbon-MOF composite transition layer, and a conductive polymer transition layer, wherein the composite current collector base is provided with gradient pores, the pore diameter of the gradient pores increasing linearly from the metal base layer to the conductive polymer transition layer, and the inner wall of the gradient pores is provided with a 1-3 nm thick Al2O3 nanocoating; The electrode membrane, including the positive electrode membrane and the negative electrode membrane, is connected by a barbed-shaped mosaic through gradient pores and has a directional conductive network inside. The active material of the positive electrode membrane is a core-shell structure with a high-nickel ternary material as the core and a lithium iron phosphate material as the shell; The active material of the negative electrode membrane is MXene-modified silicon-carbon-graphite composite powder, and the surface of the active material is coated with a 3-5nm thick nano-zirconium oxide modification layer.

[0015] The present invention also provides a battery comprising the above-mentioned dry-process battery electrode, a separator and an electrolyte; The isolation membrane is a polypropylene film coated with a 1-3 μm thick Al2O3 ceramic layer; The electrolyte consists of a solvent system and a solute, wherein the solvent system is a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1, and the solute is lithium hexafluorophosphate, and the concentration of the lithium hexafluorophosphate is 1 mol / L.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention constructs a high-performance dry-process battery electrode preparation system through multi-dimensional structural design and process innovation. Its core solution includes the coordinated design of the composite current collector and the electrode membrane: the composite current collector adopts a three-layer substrate structure of "metal substrate layer-mesoporous carbon-MOF composite transition layer-conductive polymer transition layer", and gradient pores are formed by laser drilling and Al2O3 nano-coating is deposited to enhance interface bonding; the electrode membrane is optimized for positive and negative electrode characteristics, and the positive electrode adopts a core-shell active material with a high-nickel ternary material as the core and lithium iron phosphate as the shell, and the negative electrode adopts MXene-modified silicon-carbon-graphite composite powder. Both are oriented and arranged with the assistance of a magnetic field to form a conductive network interwoven with carbon fibers and carbon nanotubes, and the electrode is made into a pole piece through gradient pressing and plasma-electrochemical dual activation process; 2. The gradient porosity of the composite current collector and the Al2O3 coating increase the peel strength to over 55N / m, a 150% improvement over traditional processes; the core-shell structured positive electrode material inhibits high-nickel side reactions, and the MXene-modified negative electrode alleviates volume expansion, with a capacity retention rate of over 90% after 500 cycles; the directional conductive network and the mesoporous transition layer work synergistically to increase the volume conductivity to over 95S / cm; the gradient pressing and dual activation process shortens the electrolyte infiltration time from 10 minutes to 3 minutes, significantly optimizing ion transfer efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a flow chart of a method for preparing a dry-process battery electrode according to the present invention; Figure 2 This is a second flow chart of a method for preparing a dry-process battery electrode according to the present invention; Figure 3 This is a schematic diagram of the first component of a dry-process battery electrode of the present invention; Figure 4 This is a second schematic diagram of the composition of a dry-process battery electrode of the present invention; Figure 5 This is a schematic diagram of the third component of a dry-process battery electrode of the present invention; The reference numerals in the drawings of the specification include: 101. Metal base layer; 102. Mesoporous carbon-MOF composite transition layer; 103. Conductive polymer transition layer; 104. Anode film; 105. Cathode film; 106. Gradient pores; 107. Al2O3 nanocoating. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention is further described below with reference to the accompanying drawings and embodiments.

[0019] Among them, the drawings are only used for illustrative purposes and represent only schematic diagrams rather than actual pictures, and should not be understood as limiting this patent; in order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of the actual product; for those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0020] A method for preparing a dry battery electrode comprises the following steps: S1. Preparation of a composite current collector: a mesoporous carbon-MOF composite transition layer 102 and a conductive polymer transition layer 103 are sequentially deposited on the surface of the metal base layer 101 to form a composite current collector substrate, a gradient pore 106 is manufactured on the composite current collector substrate throughout the entire substrate, and an Al2O3 coating 107 is deposited on the inner wall of the gradient pore to obtain a composite current collector; S2. Preparation of electrode film: comprising the following steps, S21. Preparation of positive electrode film: The core-shell structure positive electrode active material, carbon fiber, carbon nanotubes and composite binder are dry mixed in a high-speed mixer at 1500-2000 rpm for 3-5 hours; the mixed material is aligned with the aid of a 0.1-0.5T magnetic field, and fiberized at 150-200°C for 2-5 hours, and pressed into a 50-300μm thick positive electrode film; S22. Anode membrane preparation: MXene-modified anode active material, carbon fibers, carbon nanotubes, and a composite binder were dry-mixed in equal proportions in a high-speed mixer at 1500-2000 rpm for 3-5 hours. The mixed materials were aligned in a 0.1-0.5 T magnetic field, fiberized at 150-200°C for 2-5 hours, and pressed into a 50-300 μm thick anode membrane. S3: Preparation of electrode sheet: The positive electrode film, composite current collector, and negative electrode film are stacked in sequence, and subjected to gradient pressure rolling at 120-180°C, with the pressure linearly increasing from 5-10 MPa at the edge to 15-20 MPa in the center, and the rolling speed is 1-3 m / min to form the electrode sheet; S4: Preparation of dry-process battery pole pieces: The pole piece blank is subjected to plasma treatment for 30-120s at a power of 50-150W using a mixed gas of argon and oxygen in a volume ratio of 3:1. After the treatment, it is placed in a Li2SO4 solution with a concentration of 0.1mol / L and activated at a constant voltage of 0.5V for 30min to obtain a dry-process battery pole piece.

[0021] Specifically, interface enhancement is achieved through a three-level design of "composite current collector substrate + gradient pores + nanocoating". The composite current collector adopts a multilayer structure of "metal substrate layer-mesoporous carbon-MOF transition layer-conductive polymer transition layer". The mesoporous carbon-MOF transition layer improves ion adsorption capacity through high specific surface area (100-300m² / g), and the conductive polymer transition layer (poly 3,4-ethylenedioxythiophene-polystyrene sulfonate and graphene composite) optimizes electron conduction; the gradient pores (pore size 5-20μm→50-200μm) running through the substrate form a mechanical interlocking structure, and the chemical bonding effect of the 1-3nm thick Al2O3 nanocoating on the inner wall of the pore increases the peel strength to more than 55N / m, while suppressing the side reaction between the metal current collector and the electrolyte. Furthermore, the metal base layer in step S1 is aluminum foil or copper foil. When preparing the positive electrode sheet, an aluminum foil with a thickness of 5-20 μm is selected, and when preparing the negative electrode sheet, a copper foil with a thickness of 5-20 μm is selected.

[0022] Furthermore, the preparation method of the mesoporous carbon-MOF composite transition layer described in step S1 includes: dispersing the mesoporous carbon precursor and MOF powder in ethanol in a mass ratio of 7:3, and after coating, calcining at 300-500°C in a nitrogen atmosphere for 2-4 hours to form a mesoporous carbon-MOF composite transition layer. The thickness of the mesoporous carbon-MOF composite transition layer is 2-5 μm, and the mesopore size is 2-5 nm.

[0023] Furthermore, the conductive polymer transition layer in step S1 is a composite layer of poly (3,4-ethylenedioxythiophene)-polystyrene sulfonate and graphene, wherein the mass of graphene accounts for 5%-10% of the total mass of the conductive polymer transition layer, and the thickness of the conductive polymer transition layer is 1-5 μm.

[0024] Furthermore, the gradient pores are processed throughout the composite current collector substrate, including: using a laser drilling device, with the metal base layer side as the starting end and the conductive polymer transition layer side as the ending end, controlling the laser power to linearly decrease from 50-60W to 20-30W, while maintaining a drilling rate of 100-200 holes / second, so that the pore size formed increases linearly from 5-20μm on the metal base layer side to 50-200μm on the conductive polymer transition layer side.

[0025] Furthermore, the Al2O3 coating is deposited on the inner wall of the gradient pore, comprising: using trimethylaluminum and water as precursors, depositing 5-15 cycles by atomic layer deposition technology at a temperature of 100-150°C to form an Al2O3 nano-coating with a thickness of 1-3nm.

[0026] Furthermore, the preparation method of the core-shell structure positive electrode active material described in step S2 includes: dispersing high-nickel ternary material powder in a lithium iron phosphate precursor solution, hydrothermally reacting at 180-220°C for 6-12 hours and then calcining to obtain a core-shell structured positive electrode active material with high-nickel ternary material as the core and lithium iron phosphate material as the shell; adopting the "structure regulation + surface functionalization" strategy, the positive electrode uses high-nickel ternary material as the core and lithium iron phosphate as the shell, and isolates the high-nickel core from the electrolyte through a physical barrier effect, inhibiting the dissolution of transition metals, and the capacity retention rate after 500 cycles is increased to 92%; the negative electrode is modified by ball milling with 1-3% MXene nanosheets, and its two-dimensional layer structure is used to construct a three-dimensional conductive network, while buffering the 300% volume expansion of the silicon-carbon material, and the volume conductivity is increased to above 95S / cm. In the present invention, high-nickel ternary material serves as the core of the core-shell structure (such as NCM811, lithium nickel cobalt manganese oxide 811, where the number "811" represents the molar ratio of nickel (Ni), cobalt (Co), and manganese (Mn) in the positive electrode material is 8:1:1), and its high capacity advantage forms a synergistic effect with the lithium iron phosphate (LFP) shell.

[0027] In step S2, carbon fibers and carbon nanotubes are aligned under the assistance of a 0.1-0.5T magnetic field to form an orderly interwoven conductive network. This network is composed of carbon fibers with an aspect ratio of 50-100 and carbon nanotubes with a diameter of 10-20 nm, interwoven in a mass ratio of 3:1. The carbon fibers are 5-20 μm long, and the carbon nanotubes are 10-50 μm long. The carbon fibers with an aspect ratio of 50-100 (5-20 μm in length) serve as the backbone, providing mechanical support and forming the primary conductive pathway. This aspect ratio balances mechanical strength and conductive continuity, avoiding uneven dispersion due to excessive length or network breakage due to excessive shortness. Carbon nanotubes with a diameter of 10-20 nm and a length of 10-50 μm fill the interstices between the carbon fibers, enhancing interfacial conductivity through nanoscale contact. The diameter of the carbon nanotubes is consistent with the optimal range (10-20 nm) found in existing research for optimizing carrier transport.

[0028] A 3:1 mass ratio: carbon fibers serve as the primary backbone, while carbon nanotubes serve as secondary conductive bridges. This ratio has been experimentally verified to achieve a volume conductivity of ≥95S / cm. Oriented by a 0.1-0.5T magnetic field, the carbon fibers align parallel to the membrane surface, while the carbon nanotubes connect in three dimensions, forming a structured conductive network that significantly reduces ion transport resistance.

[0029] The preparation method of the MXene-modified negative electrode active material in step S2 includes: mixing the silicon-carbon composite material and graphite in a mass ratio of 1:3-1:5, adding 1-3% by mass of MXene nanosheets and modifying them by ball milling to obtain the MXene-modified negative electrode active material.

[0030] Furthermore, the composite binder is composed of polytetrafluoroethylene and multi-arm polyethylene glycol in a mass ratio of 3:1, and the total mass of the composite binder accounts for 2%-4% of the total mass of the mixed materials.

[0031] The entire process utilizes a dry process (without organic solvents), achieving optimal performance through a "fiberization treatment + plasma-electrochemical dual activation" process. Fiberization (150-200°C) enhances the stability of the binder network, plasma treatment introduces hydrophilic groups, and constant voltage activation with a 0.1 mol / L lithium sulfate solution (0.5 V, 30 minutes) promotes the formation of a stable SEI film, ultimately achieving optimal electrode density uniformity and electrochemical stability.

[0032] The present invention also provides a dry-process battery electrode, which is prepared by the above-mentioned preparation method, comprising: A composite current collector, comprising, from the inside out, a metal base layer, a mesoporous carbon-MOF composite transition layer, and a conductive polymer transition layer, wherein the composite current collector base is provided with gradient pores, the pore diameter of the gradient pores increasing linearly from the metal base layer to the conductive polymer transition layer, and the inner wall of the gradient pores is provided with a 1-3 nm thick Al2O3 nanocoating; The electrode membrane, including the positive electrode membrane 105 and the negative electrode membrane 104, is connected by a barbed-shaped interlocking connection through gradient pores, and has a directional conductive network inside. The active material of the positive electrode membrane is a core-shell structure with a high-nickel ternary material as the core and a lithium iron phosphate material as the shell; The active material of the negative electrode membrane is MXene-modified silicon-carbon-graphite composite powder, and the surface of the active material is coated with a 3-5nm thick nano-zirconium oxide modification layer.

[0033] The present invention also provides a battery comprising the above-mentioned dry-process battery electrode, a separator and an electrolyte; The isolation membrane is a polypropylene film coated with a 1-3 μm thick Al2O3 ceramic layer; The electrolyte consists of a solvent system and a solute, wherein the solvent system is a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1, and the solute is lithium hexafluorophosphate, and the concentration of the lithium hexafluorophosphate is 1 mol / L.

[0034] Example 1 Step S1: Preparation of composite current collector An 8μm thick aluminum foil (positive electrode) was selected; the mesoporous carbon precursor and ZIF-67 were dispersed in ethanol at a mass ratio of 7:3. After coating, the mixture was calcined at 350°C in a nitrogen atmosphere for 2.5 hours to form a 2μm thick mesoporous carbon-MOF composite transition layer (mesopores 2nm, specific surface area 150m² / g); a poly (3,4-ethylenedioxythiophene)-polystyrene sulfonate solution doped with 5% graphene was coated to form a 1μm thick conductive polymer transition layer. Laser drilling: power reduced from 50 W to 20 W, drilling rate 100 holes / s, pore diameter 5 μm → 50 μm; atomic layer deposition 5 cycles to form a 1 nm thick Al2O3 coating. Step S2: Preparation of positive electrode film NCM811 was dispersed in a lithium iron phosphate precursor, hydrothermally reacted at 180°C for 6 hours, and then calcined (core-shell mass ratio 3:1, shell thickness 5nm), and coated with 3nm zirconium oxide. 93% active material, 5% carbon fiber (aspect ratio 50, length 5μm), 1% carbon nanotube (diameter 10nm, length 10μm) and 2% composite binder (polytetrafluoroethylene: multi-arm polyethylene glycol = 3:1) were mixed in a high-speed mixer at 1500rpm for 3 hours; they were oriented in a 0.1T magnetic field, fiberized at 150℃ for 2 hours, and pressed into a 50μm thick positive electrode film. Steps S3-S4: 120℃ gradient roller pressing (5MPa at the edge→15MPa at the center, roller speed 1m / min); plasma treatment (50W power, 30s, Ar / O2=3:1); activation with 0.1mol / LLi2SO4 solution at 0.5V for 30min.

[0035] Performance testing: Peel strength 55N / m, volume conductivity 95S / cm, electrolyte immersion time 4min, 500 cycle retention rate 90%, 1C discharge capacity 155mAh / g, electrode internal resistance 45mΩ・cm, ion transfer rate 3.2×10⁻ 4 cm / s, low temperature (-20℃) discharge capacity retention rate is 80%. Example 2 Step S1: Preparation of composite current collector A 12μm thick aluminum foil was selected; the mesoporous carbon precursor and ZIF-67 were dispersed in a ratio of 7:3, and after coating, they were calcined at 400°C in a nitrogen atmosphere for 3 hours to form a 3μm thick mesoporous carbon-MOF composite transition layer (mesopores 3nm, specific surface area 200m² / g); a poly (3,4-ethylenedioxythiophene)-polystyrene sulfonate solution doped with 8% graphene was coated to form a 3μm thick conductive polymer transition layer. Laser drilling: power reduced from 55 W to 25 W, drilling rate 150 holes / s, pore diameter 10 μm → 150 μm; atomic layer deposition 10 cycles to form a 2 nm thick Al2O3 coating. Step S2: Preparation of positive electrode film NCM811 was dispersed in a lithium iron phosphate precursor, hydrothermally reacted at 200°C for 9 hours, and then calcined (core-shell mass ratio 3:1, shell thickness 8nm), and coated with 4nm zirconium oxide. 92% active material, 5% carbon fiber (aspect ratio 80, length 12μm), 3% carbon nanotubes (diameter 15nm, length 30μm) and 3% composite binder were mixed in a high-speed mixer at 1800rpm for 4 hours; they were oriented in a 0.3T magnetic field, fiberized at 180℃ for 3.5 hours, and pressed into a 180μm thick positive electrode film. Steps S3-S4: 150℃ gradient roller pressing (8MPa at the edge → 18MPa at the center, roller speed 2m / min); plasma treatment (100W power, 60s, Ar / O2=3:1); activation with 0.1mol / LLi2SO4 solution at 0.5V for 30min. Performance test: Peel strength 58N / m, volume conductivity 98S / cm, electrolyte immersion time 3min, 500 cycle retention rate 92%, 1C discharge capacity 158mAh / g, electrode internal resistance 42mΩ・cm, ion transfer rate 3.5×10⁻ 4 cm / s, and the low temperature (-20°C) discharge capacity retention rate is 82%. Example 3 Step S1: Preparation of composite current collector A 20μm thick aluminum foil was selected; the mesoporous carbon precursor and ZIF-67 were dispersed in a ratio of 7:3, and after coating, they were calcined at 500°C in a nitrogen atmosphere for 4 hours to form a 5μm thick mesoporous carbon-MOF composite transition layer (mesopores 5nm, specific surface area 300m² / g); a poly (3,4-ethylenedioxythiophene)-polystyrene sulfonate solution doped with 10% graphene was coated to form a 5μm thick conductive polymer transition layer. Laser drilling: power reduced from 60W to 30W, drilling rate 200 holes / s, pore diameter 20μm→200μm; atomic layer deposition 15 cycles to form a 3nm thick Al2O3 coating. Step S2: Preparation of positive electrode film NCM811 was dispersed in a lithium iron phosphate precursor, hydrothermally reacted at 220°C for 12 hours, and then calcined (core-shell mass ratio 3:1, shell thickness 10 nm), and coated with 5 nm zirconium oxide. 91% active material, 5% carbon fiber (aspect ratio 100, length 20μm), 4% carbon nanotubes (diameter 20nm, length 50μm) and 4% composite binder are mixed in a high-speed mixer at 2000rpm for 5 hours; they are oriented in a 0.5T magnetic field, fiberized at 200℃ for 5 hours, and pressed into a 300μm thick positive electrode film.

[0036] Steps S3-S4: 180℃ gradient roller pressing (10MPa at the edge→20MPa at the center, roller speed 3m / min); plasma treatment (150W power, 120s, Ar / O2=3:1); activation with 0.1mol / LLi2SO4 solution at 0.5V for 30min.

[0037] Performance testing: Peel strength 56N / m, volume conductivity 96S / cm, electrolyte immersion time 5min, 500 cycle retention rate 91%, 1C discharge capacity 157mAh / g, electrode internal resistance 44mΩ・cm, ion transfer rate 3.3×10⁻ 4 cm / s, and the low temperature (-20°C) discharge capacity retention rate is 81%. Comparative Example 1 Key differences: The composite current collector has no gradient pores and inner wall Al2O3 coating, and the other parameters are consistent with Example 2. Performance testing: Peel strength 32N / m, volume conductivity 97S / cm, electrolyte immersion time 8min, 500 cycle retention rate 91%, 1C discharge capacity 157mAh / g, electrode internal resistance 43mΩ・cm, ion transfer rate 3.4×10⁻ 4 cm / s, and the low temperature (-20°C) discharge capacity retention rate is 81%. Comparative Example 2 Key difference: The positive electrode active material is pure NCM811 (without lithium iron phosphate shell), and the other parameters are consistent with Example 2. Performance testing: Peel strength 57N / m, volume conductivity 98S / cm, electrolyte immersion time 3min, 500 cycle retention rate 75%, 1C discharge capacity 156mAh / g, electrode internal resistance 42mΩ・cm, ion transfer rate 3.5×10⁻ 4 cm / s, and the low temperature (-20°C) discharge capacity retention rate is 82%. Comparative Example 3 Key difference: The conductive network has no magnetic field orientation (random dispersion), and the remaining parameters are consistent with Example 2.

[0038] Performance testing: Peel strength 58N / m, volume conductivity 62S / cm, electrolyte immersion time 3min, 500 cycle retention rate 92%, 1C discharge capacity 158mAh / g, electrode internal resistance 85mΩ・cm, ion transfer rate 3.5×10⁻ 4 cm / s, and the low temperature (-20°C) discharge capacity retention rate is 82%. Comparative Example 4 Key difference: The composite current collector does not have a mesoporous carbon-MOF transition layer, and the other parameters are consistent with Example 2 Performance testing: Peel strength 57N / m, volume conductivity 97S / cm, electrolyte immersion time 3min, 500 cycle retention rate 92%, 1C discharge capacity 158mAh / g, electrode internal resistance 43mΩ・cm, ion transfer rate 1.8×10⁻ 4 cm / s, low temperature (-20℃) discharge capacity retention rate is 65%.

[0039] Performance test results summary table Analysis and explanation: The peel strengths of the three examples were 55 N / m, 58 N / m, and 56 N / m, respectively, all meeting the requirement of "≥55 N / m", verifying the enhanced interfacial bonding strength of the composite current collector structure of "metal substrate layer-mesoporous carbon-MOF transition layer-conductive polymer transition layer + gradient pores + Al2O3 coating"; Volume conductivity: 95 S / cm, 98 S / cm, and 96 S / cm, respectively, all meeting the "≥95 S / cm" standard, demonstrating that the magnetic field-assisted orientation-formed carbon fiber-carbon nanotube conductive network (aspect ratio 50-100, diameter 10-20 nm, mass ratio 3:1) can steadily improve electron transport efficiency; Cycle stability: The capacity retention rate after 500 cycles is 90%-92%, meeting the requirement of "≥90%", reflecting the inhibitory effect of the positive electrode core-shell structure (high nickel ternary as the core and lithium iron phosphate as the shell) on side reactions.

[0040] Comparative Example 1 (no gradient porosity and Al2O3 coating): The peel strength decreased from 58 N / m in Example 2 to 32 N / m, and the electrolyte infiltration time was extended from 3 min to 8 min, demonstrating that the mechanical intercalation of the gradient porosity and the chemical bonding of the Al2O3 coating are the key factors in improving interfacial adhesion and electrolyte wettability. Comparative Example 2 (no cathode core-shell structure): The capacity retention rate dropped to 75% after 500 cycles, verifying that the physical isolation effect of the lithium iron phosphate shell in the core-shell structure on the high-nickel ternary material can effectively inhibit transition metal dissolution and side reactions; Comparative Example 3 (without magnetic field-assisted orientation): The volume conductivity dropped sharply to 62 S / cm, and the internal resistance of the electrode increased to 85 mΩ・cm, indicating that magnetic field orientation is a key process to ensure the regularity of the conductive network and reduce the resistance to electron transmission. Comparative Example 4 (no mesoporous carbon-MOF composite transition layer): ion transmission rate dropped to 1.8×10⁻ 4 cm / s, and the low-temperature discharge capacity retention rate dropped to 65%, reflecting the optimization effect of the mesoporous structure (2-5nm) of the mesoporous carbon-MOF transition layer on ion adsorption and transport.

[0041] The above are only embodiments of the present invention, and the circuits, electronic components and modules involved are all prior art, which can be fully implemented by those skilled in the art. It is needless to say that the content protected by this application does not involve improvements to software and methods. Common knowledge such as the specific structures and characteristics known in the scheme are not described in detail here. Ordinary technicians in the field are aware of all common technical knowledge in the technical field of the invention before the application date or priority date, can obtain all prior art in the field, and have the ability to apply conventional experimental means before that date. Ordinary technicians in the field can improve and implement this scheme in combination with their own abilities under the inspiration given by this application. Some typical known structures or known methods should not become obstacles for ordinary technicians in the field to implement this application. It should be pointed out that for those skilled in the art, without departing from the structure of the present invention, several variations and improvements can be made, which should also be regarded as the scope of protection of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing a dry-process battery electrode, characterized in that: The following steps are included: S1. Preparation of a composite current collector: depositing a mesoporous carbon-MOF composite transition layer and a conductive polymer transition layer on the surface of a metal substrate to form a composite current collector substrate, creating gradient pores throughout the composite current collector substrate, and depositing an Al2O3 coating on the inner wall of the gradient pores to obtain a composite current collector; S2. Preparation of electrode membrane: The following steps are included: S21. Preparation of positive electrode film: The core-shell structure positive electrode active material, carbon fiber, carbon nanotubes and composite binder are dry mixed in a high-speed mixer at 1500-2000 rpm for 3-5 hours; the mixed material is aligned with the aid of a 0.1-0.5T magnetic field, and fiberized at 150-200°C for 2-5 hours, and pressed into a 50-300μm thick positive electrode film; S22. Anode membrane preparation: MXene-modified anode active material, carbon fibers, carbon nanotubes, and a composite binder were dry-mixed in equal proportions in a high-speed mixer at 1500-2000 rpm for 3-5 hours. The mixed materials were aligned in a 0.1-0.5 T magnetic field, fiberized at 150-200°C for 2-5 hours, and pressed into a 50-300 μm thick anode membrane. S3: Preparation of electrode sheet: The positive electrode film, composite current collector, and negative electrode film are stacked in sequence, and subjected to gradient pressure rolling at 120-180°C, with the pressure linearly increasing from 5-10 MPa at the edge to 15-20 MPa in the center, and the rolling speed is 1-3 m / min to form the electrode sheet; S4: Preparation of dry-process battery pole pieces: The pole piece blank is subjected to plasma treatment for 30-120s at a power of 50-150W using a mixed gas of argon and oxygen in a volume ratio of 3:

1. After the treatment, it is placed in a Li2SO4 solution with a concentration of 0.1mol / L and activated at a constant voltage of 0.5V for 30min to obtain a dry-process battery pole piece.

2. The method for preparing a dry-process battery electrode according to claim 1, wherein: The metal base layer in step S1 is aluminum foil or copper foil. When preparing the positive electrode sheet, an aluminum foil with a thickness of 5-20 μm is selected, and when preparing the negative electrode sheet, a copper foil with a thickness of 5-20 μm is selected.

3. The method for preparing a dry-process battery electrode according to claim 1, wherein: The preparation method of the mesoporous carbon-MOF composite transition layer described in step S1 includes: dispersing a mesoporous carbon precursor and MOF powder in ethanol in a mass ratio of 7:3, and after coating, calcining at 300-500°C in a nitrogen atmosphere for 2-4 hours to form a mesoporous carbon-MOF composite transition layer. The thickness of the mesoporous carbon-MOF composite transition layer is 2-5 μm, and the mesopore size is 2-5 nm.

4. The method for preparing a dry-process battery electrode according to claim 1, wherein: The conductive polymer transition layer in step S1 is a composite layer of poly (3,4-ethylenedioxythiophene)-polystyrene sulfonate and graphene, wherein the mass of graphene accounts for 5%-10% of the total mass of the conductive polymer transition layer, and the thickness of the conductive polymer transition layer is 1-5 μm.

5. The method for preparing a dry-process battery electrode according to claim 1, wherein: The method of processing gradient pores running through the entire composite current collector substrate includes: using a laser drilling device, with the metal base layer side as the starting end and the conductive polymer transition layer side as the ending end, controlling the laser power to linearly decrease from 50-60W to 20-30W, while maintaining a drilling rate of 100-200 holes / second, so that the pore size formed increases linearly from 5-20μm on the metal base layer side to 50-200μm on the conductive polymer transition layer side.

6. The method for preparing a dry-process battery electrode according to claim 1, wherein: The Al2O3 coating is deposited on the inner wall of the gradient pore, comprising: using trimethylaluminum and water as precursors, depositing 5-15 cycles by atomic layer deposition technology at a temperature of 100-150°C to form an Al2O3 nano-coating with a thickness of 1-3nm.

7. The method for preparing a dry-process battery electrode according to claim 1, wherein: The method for preparing the core-shell structure positive electrode active material in step S2 comprises: dispersing high nickel ternary material powder in a lithium iron phosphate precursor solution, hydrothermally reacting at 180-220° C. for 6-12 hours, and then calcining to obtain a core-shell structure positive electrode active material with the high nickel ternary material as the core and the lithium iron phosphate material as the shell; In step S2, the carbon fibers and carbon nanotubes are aligned in a 0.1-0.5 T magnetic field to form an orderly interwoven oriented conductive network, wherein the oriented conductive network is formed by interweaving carbon fibers with an aspect ratio of 50-100 and carbon nanotubes with a diameter of 10-20 nm in a mass ratio of 3:1, with the carbon fibers having a length of 5-20 μm and the carbon nanotubes having a length of 10-50 μm. The preparation method of the MXene-modified negative electrode active material in step S2 includes: mixing the silicon-carbon composite material and graphite in a mass ratio of 1:3-1:5, adding 1-3% by mass of MXene nanosheets and modifying them by ball milling to obtain the MXene-modified negative electrode active material.

8. The method for preparing a dry-process battery electrode according to claim 1, wherein: The composite binder is composed of polytetrafluoroethylene and multi-arm polyethylene glycol in a mass ratio of 3:1, and the total mass of the composite binder accounts for 2%-4% of the total mass of the mixed materials.

9. A dry-process battery electrode, prepared by the preparation method according to any one of claims 1 to 8, characterized in that: include: A composite current collector, comprising, from the inside out, a metal base layer, a mesoporous carbon-MOF composite transition layer, and a conductive polymer transition layer, wherein the composite current collector base is provided with gradient pores, the pore diameter of the gradient pores increasing linearly from the metal base layer to the conductive polymer transition layer, and the inner wall of the gradient pores is provided with a 1-3 nm thick Al2O3 nanocoating; The electrode membrane, including the positive electrode membrane and the negative electrode membrane, is connected by a barbed-shaped mosaic through gradient pores and has a directional conductive network inside. The active material of the positive electrode membrane is a core-shell structure with a high-nickel ternary material as the core and a lithium iron phosphate material as the shell; The active material of the negative electrode membrane is MXene-modified silicon-carbon-graphite composite powder, and the surface of the active material is coated with a 3-5nm thick nano-zirconium oxide modification layer.

10. A battery, characterized in that: The dry-process battery electrode, the separator and the electrolyte according to claim 9 are included; The isolation membrane is a polypropylene film coated with a 1-3 μm thick Al2O3 ceramic layer; The electrolyte consists of a solvent system and a solute, wherein the solvent system is a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1, and the solute is lithium hexafluorophosphate with a concentration of 1 mol / L.

Citation Information

Patent Citations

  • Lithium ion battery and preparation method thereof

    CN111384387A

  • Sulfur-based positive electrode material of all-solid-state battery and preparation method of sulfur-based positive electrode material

    CN114512640A

  • Method for integrally preparing solid-state battery through 3D printing

    CN116277926A

  • Integrated composite positive pole piece with solid electrolyte layer and preparation method of integrated composite positive pole piece

    CN118867139A

  • Thermo-electric capacitor

    US20210366659A1

Cited By

  • Positive electrode composite structure, preparation method thereof, battery and application

    CN121905799A